The Influence of Regret Aversion and Risk Tolerance on Cryptocurrency Investment Decisions: The Mediating Role of Risk Perception and the Moderating Effect of Income Perception (A Case Study on Generation Z in Bali) - Ni Nyoman Ayu Cahyani; Yunita, Putu Irma (Universitas Muhammadiyah Pontianak, 2026)
The rise of digital technology in the Industrial Revolution 4.0 era has increased Generation Z’s interest in cryptocurrency investment, despite its high risks. This study analyzes the effects of regret aversion, risk tolerance, and risk perception on investment decisions, with income perception as a moderator. Using SmartPLS 3.0 and 125 respondents, results show no significant effect of psychological factors on investment decisions. Risk perception fails to mediate, and income perception does not moderate the relationships. These findings highlight the limited role of psychological factors, suggesting stronger external influences and the need for enhanced financial psychology literacy and future research on social aspects.